2020
DOI: 10.1088/1757-899x/830/2/022052
|View full text |Cite
|
Sign up to set email alerts
|

Bolt connection performance post fire in steel bridges

Abstract: Fire events reduce the strength of the steel structure on the bridge and can cause collapse which results in losses, so it is necessary to consider the effects of fire when planning construction. Considering that the joints affect the performance of steel structures, the results of research on the performance of steel beams need to be augmented by testing the post-fire girder bridge bolt connection performance. Structural tests will be carried out on six specimens of bridge steel beam elements with high qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The test results show that the beam model with a center load of 38kN in the center of the span can withstand temperatures of 550°C for 120 minutes without significant reduction with a deflection of about 10 mm and is much larger than a similar specimen burning at the same temperature with a load of 19kN. Burning at a target temperature of 900°C for approximately 20 minutes showed that specimens with a load of 19kN experienced a very large deflection with a deflection of up to 150 mm, while specimens with a load of 38kN collapsed due to lateral flexural [3]. The above results are consistent with the test results numerical (Gunadi, 2016), which proves that at a temperature of 600°C, the beam's stiffness and flexural capacity has very significantly decreased.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The test results show that the beam model with a center load of 38kN in the center of the span can withstand temperatures of 550°C for 120 minutes without significant reduction with a deflection of about 10 mm and is much larger than a similar specimen burning at the same temperature with a load of 19kN. Burning at a target temperature of 900°C for approximately 20 minutes showed that specimens with a load of 19kN experienced a very large deflection with a deflection of up to 150 mm, while specimens with a load of 38kN collapsed due to lateral flexural [3]. The above results are consistent with the test results numerical (Gunadi, 2016), which proves that at a temperature of 600°C, the beam's stiffness and flexural capacity has very significantly decreased.…”
Section: Introductionmentioning
confidence: 88%
“…At this temperature, the maximum stress that can be achieved is far below the yield stress of the material [4]. Another study is that the steel profile bolt joints that are burned and subjected to a flexural test with Universal Testing Machine (UTM) have been shown to reduce the plate friction force by 12%, thereby reducing the post-fire friction performance [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations